An Overview of Environmental Management Regulations in the Bogor City, West Java, Indonesia - Tjahjo Tri Hartono; Renea Shinta Aminda; Almyanti Ningrum; Ibrahim Fajar; Muhammad Jiddan Aziz; Aidha Zulaikha; Budi Susetyo; Sukma Laksita Rahma; Gunawan Ismail (Universitas Ibn Khaldun Bogor, 2023)
The Bogor City Government seeks to regulate the implementation of environmental protection and management in accordance with the principles of environmental protection and management and is guided by higher statutory regulations as stipulated in regional regulations. Re-examine Regional Regulation Number 1 of 2014 to ensure that these regional regulations are in accordance with established standards, plans, and norms. The approach used in this research is the evaluation of statutory regulations, which includes an inventory of materials, the evaluation of statutory regulations using six dimensions in which there are several variables and assessment indicators, and formulating recommendations to provide solutions to existing problems in statutory regulations. The assessment of Bogor City Regional Regulation Number 1 of 2014 concerning Environmental Protection and Management refers to several dimensions of evaluation of statutory regulations resulting in a recommendation, namely that this statutory regulations is urgently revoked and needs to be included in the long list of the 5-year Prolegda for its replacement statutory regulations. Several statutory regulations have become material for evaluating Bogor City Regional Regulation Number 1 of 2014 concerning related environmental protection and management, especially since the Central Government issued a policy regarding job creation. It is recommended that an academic manuscript be prepared on the Draft Regional Regulations for the City of Bogor concerning the Implementation of Environmental Protection and Management.